Understanding the overlap between cyberbullying and cyberhate perpetration: Moderating effects of toxic online disinhibition. (5th July 2019) - Wachs, Sebastian; Wright, Michelle F.; Vazsonyi, Alexander T.
Abstract: Background: Problem behaviour theory postulates that different forms of norm violations cluster and can be explained by similar antecedents. One such cluster may include cyberbullying and cyberhate perpetration. A potential explanatory mechanism includes toxic online disinhibition, characterised by anonymity, an inability to empathise and to recognise and interpret social cues. The current study to develop a better understanding of the relationship between cyberhate and cyberbullying to inform effective intervention and prevention efforts. Aims: To test the link between cyberbullying and cyberhate and whether this relationship was moderated by toxic online disinhibition. Methods: Self‐report questionnaires on cyberbullying, cyberhate, and toxic online disinhibition were completed by 1, 480 adolescents between 12 and 17 years old ( M = 14.21 years; SD = 1.68). Results: Increases in cyberbullying perpetration and toxic online disinhibition were positively related to cyberhate perpetration. Furthermore, cyberbullies reported more cyberhate perpetration when they reported higher levels of toxic online disinhibition and less frequent cyberhate perpetration when they reported lower levels of toxic online disinhibition. Conclusion: The current study provides evidence of a possible link between cyberbullying and cyberhate perpetration, moderated by toxic online disinhibition. This suggests that, to be effective, prevention and intervention programmes should (i) consider the co‐occurrence of varying forms of cyberaggression and (ii) consider potential effects of the online environment on aggressive online behaviour among young people.